The Forensic Medicine in Peru - Avendaño, L. (1918)
A new era in the teaching of legal medicine at the Faculty of Medicine of Lima starts today. Thanks to the generosity of the Government, with the valuable quota provided by the Faculty of Medicine, and with the dedication and successful work of the Commission for the construction of this building, the students of the School of San Fernando will henceforth learning this important discipline of medical science, according to the progress made in recent decades, and subject to the requirements imposed by the continuing transformation of the various areas of law.